HEALTH STATUS OF BACKYARD POULTRY IN BASTAR DISTRICT OF CHHATTISGARH - Chaturvedi, AK; Lal, Niranjan; Chandra, Mahesh; Hussain, Khalid (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The Present study was conducted to assess health care status of tribal backyard poultry in Bastar district of Chhattisgarh. A multi-stage random sampling procedure was used to select 120 respondents (12 respondents per village) in the purposively selected study area. A structured interview schedule duly pre-tested and validated was used to elicit information from the respondents. Data collected were analyzed using statistical tools like frequency counts and percentage. The results showed that 86.67% respondents reported major cause of mortality was due to Attack by predators, 66.67% respondents reported disease encountered by avian influenza, 46.67% respondents treated their sick bird by herself with ethno-veterinary medicines and 48.33% vaccinate against New castle disease (ND) with the help of government supplied vaccines.
Keywords: Health care; Backyard poultry; Chhattisgarh